People Ops Lessons in Culture and Leadership From Building Startups - Caldwell, Patrick (Berkeley, CA : Apress : Imprint: Apress, 2023)
Learn to deal with difficult employee demands, navigate layoffs, address the gender pay gap, protect your time and wellbeing, and discover what candidates really think about recruitment processes. People Ops is a collection of candid lessons, stories, and principles in leadership, people, and culture from startup environments. It reveals the hard truths and sometimes uncomfortable realities that we all know exist but struggle to articulate. For decades, business and HR leaders have struggled to navigate the complexities of managing people and teams within startups and scaling companies, instead relying on the broad rhetoric of management theory to tackle these challenges or leaning on their networks of leaders who have encountered these challenges before. In parallel, the HR industry has been undergoing a transformation with the growth of People Operations. It's a distinct field in HR that relentlessly focuses on engagement, culture, automation and putting people at the heart of all business operations. At the intersection of startups and people operations is an increasingly ambiguous business challenge for how startups can apply leading people practices to drive their growth, rather than in spite of their growth. People Ops is a tactical companion for business and People Operations leaders designed to support them in their roles, spark inspiration and challenge conventional thinking. It supplements author Patrick Caldwell's own experience across multiple startups with stories and examples from his network of investors, CEOs, Founders and C-Level HR executives. .
1. Building From Scratch -- 2. Leadership -- 3. Culture -- 4. Inclusion -- 5. Recruitment -- 6. Reward -- 7. Learning -- 8. Performance -- 9. Remote Working -- 10. Your Career -- 11. TL;DR. .
Keywords: New business enterprises; Venture capital; Personnel management; Career development; Employee health promotion; Strategic planning; Leadership; Start-Ups and Venture Capital; Human Resource Management; Careers in Business and Management; Employee Health and Wellbeing; Human Resource Development; Business Strategy and Leadership